2017
DOI: 10.1111/jan.13290
|View full text |Cite
|
Sign up to set email alerts
|

Intentional partnering: a grounded theory study on developing effective partnerships among nurse and physician managers as they co‐lead in an evolving healthcare system

Abstract: Intentional partnering elucidates the relational components of working together and the strategizing that occurs as each partner deliberates on what he or she is willing to accept, risk and put into place to reap the benefits of collaborating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The proposed model for dyad leadership success concepts from the extant literature not specifically identified by the participants in our study is identified by numbers identifying the specific reference cited in the text. The key terms referred to include partnering intelligence (accomplishment of mutually beneficial objectives through trust, interdependence, self-disclosure and feedback, mutuality, comfort with change, and future orientation), 36 intentional partnering (taking a broader perspective, taking risk together, and actively developing shared responsibilities), 24 professional and management logics (the former referring to expertise and certification-based authority and the latter to former hierarchical positions), 5 and moral imagination (considering a situation's context, nuances, and reimagining the framework to expand one's conceptualization of the problem and its solution). 37 144…”
Section: Mindset and Attitudesmentioning
confidence: 99%
See 4 more Smart Citations
“…The proposed model for dyad leadership success concepts from the extant literature not specifically identified by the participants in our study is identified by numbers identifying the specific reference cited in the text. The key terms referred to include partnering intelligence (accomplishment of mutually beneficial objectives through trust, interdependence, self-disclosure and feedback, mutuality, comfort with change, and future orientation), 36 intentional partnering (taking a broader perspective, taking risk together, and actively developing shared responsibilities), 24 professional and management logics (the former referring to expertise and certification-based authority and the latter to former hierarchical positions), 5 and moral imagination (considering a situation's context, nuances, and reimagining the framework to expand one's conceptualization of the problem and its solution). 37 144…”
Section: Mindset and Attitudesmentioning
confidence: 99%
“…54 The concept of "intentional partnering" includes taking a broader perspective, taking risk together, and actively developing shared responsibilities. 24 Similarly, "partnering intelligence" that refers to accomplishment of mutually beneficial objectives involving trust, interdependence, self-disclosure and feedback, mutuality, comfort with change, and future orientation 36 is believed to be integral for achieving synergy in a dyad model. 32 With these in place, the tactical approaches such as frequent meetings and active listening would be relatively easy to emerge.…”
Section: Interpersonal Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations